2014
DOI: 10.1111/eci.12293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and gender on microvascular function

Abstract: During adolescence, PORH is a function of age. At higher age, microvascular reactivity considerably depends on gender, whereas no sex differences are present at younger ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
(46 reference statements)
0
12
1
Order By: Relevance
“…We found that the hyperemic response to transient ischemia is greater and more prolonged in males than in females. It is well documented that gender has a significant impact on POHR readings not only in large arteries but also in the microcirculation of the skin . Our results suggest that in a challenged situation the vasodilator (FMD and ascending dilatation) capacity of the gingival vessels may be higher in males.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We found that the hyperemic response to transient ischemia is greater and more prolonged in males than in females. It is well documented that gender has a significant impact on POHR readings not only in large arteries but also in the microcirculation of the skin . Our results suggest that in a challenged situation the vasodilator (FMD and ascending dilatation) capacity of the gingival vessels may be higher in males.…”
Section: Discussionmentioning
confidence: 49%
“…It is well documented that gender has a significant impact on POHR readings not only in large arteries [43][44][45] but also in the microcirculation of the skin. 46,47 Our results suggest that in a challenged situation the F I G U R E 8 Cumulated blood flow changes during a five-second interval (TOI2) of horizontal (A), vertical (B), and papilla base (C) compression and subsequently for twenty minutes (TOI3-7), grouped by gender. Perfusion values within a TOI were averaged.…”
Section: Discussionmentioning
confidence: 91%
“…Concerning a gender impact on TiVi values, men showed significant higher TiVi values representing a higher subepidermal concentration of red blood cells and therefore a higher blood circulation than women. Previous studies have also observed such differences in microcirculation between both sexes . The gender impact on development of hand eczema is still under discussion.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also observed such differences in microcirculation between both sexes. 31,32 The gender impact on development of hand eczema is still under discussion. There are studies which indicate to a higher risk for women, but others did not.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed an overall neutral effect of COX inhibition on skin PORH [33], suggesting no involvement of prostanoids. PORH is inversely associated with age in children and adolescents [71], attenuated in smokers [63], and in hypertension in which it may be restored after antihypertensive therapy [62,74]. Similarly, statins have been shown to improve PORH in hypercholesterolemic patients [4] but not in central obesity [14].…”
Section: Postocclusive Reactive Hyperemiamentioning
confidence: 99%